The stay-green phenotype of TaNAM-RNAi wheat plants is associated with maintenance of chloroplast structure and high enzymatic antioxidant activity - Checovich, Mariana Leonela (2016)
TaNAM transcription factors play an important role in controlling senescence, which in turn, influences the delivery of nitrogen, iron and other elements to the grain of wheat (Triticum aestivum) plants, thus contributing to grain nutritional value. While lack or diminished expression of TaNAMs determines a stay-green phenotype, the precise effect of these factors on chloroplast structure has not been studied. In this work we focused on the events undergone by chloroplasts in two wheat lines having either control or diminished TaNAM expression due to RNA interference (RNAi). It was found that in RNAi plants maintenance of chlorophyll levels and maximal photochemical efficiency of photosystem II were associated with lack of chloroplast dismantling. Flow cytometer studies and electron microscope analysis showed that RNAi plants conserved organelle ultrastructure and complexity. It was also found that senescence in control plants was accompanied by a low leaf enzymatic antioxidant activity. Lack of chloroplast dismantling in RNAi plants was associated with maintenance of protein and iron concentration in the flag leaf, the opposite being observed in control plants. These data provide a structural basis for the observation that down regulation of TaNAMs confers a functional stay-green phenotype and indicate that the low export of iron and nitrogen from the flag leaf of these plants is concomitant, within the developmental window studied, with lack of chloroplast degradation and high enzymatic antioxidant activity.